MARK TWAIN IN THE SOCIAL CONTEXT OF THE XIX CENTURY (Konferensiyalar | Conferences, 2024)
The novel chosen for examining the realistic elements in Twain's writing, The Adventure of Tom Sawyer, depicts his early recollections. The book teaches readers about the morals and ideals of the era while telling the story of two young boys who love to go on adventures.